1997
DOI: 10.1016/s1010-7940(97)00105-x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracotomy and thoracoscopy: postoperative pulmonary function, pain and chest wall complaints

Abstract: Post-thoracotomy pain can be effectively controlled with epidural analgesia and pain intensity is no higher than in patients after thoracoscopy who are managed with patient controlled analgesia. FVC is slightly more decreased after thoracotomy during the early postoperative period. FVC and FEV 1 approach the predicted values after four months in both groups. The rate of persistent pain is similar after thoracoscopy and thoracotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
60
0
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(78 citation statements)
references
References 19 publications
9
60
0
9
Order By: Relevance
“…Two prospective trials found no differences in the incidence of PTPS when VATS was used compared with the classic posterolateral approach or the muscle-sparing posterolateral approach. 20,21 One retrospective study concluded that VATS reduced PTPS when compared with a muscle-sparing incision. 22 Other intraoperative surgical techniques that have been associated with reduced incidence of PTPS are harvesting an intercostal muscle flap, free dissection of intercostal nerves, and the use of intracostal sutures for closing the incision.…”
Section: Surgical Factorsmentioning
confidence: 99%
“…Two prospective trials found no differences in the incidence of PTPS when VATS was used compared with the classic posterolateral approach or the muscle-sparing posterolateral approach. 20,21 One retrospective study concluded that VATS reduced PTPS when compared with a muscle-sparing incision. 22 Other intraoperative surgical techniques that have been associated with reduced incidence of PTPS are harvesting an intercostal muscle flap, free dissection of intercostal nerves, and the use of intracostal sutures for closing the incision.…”
Section: Surgical Factorsmentioning
confidence: 99%
“…There is little consensus regarding the impact that the type of surgery has on the clinical outcome in terms of PTPS. Some studies showing there being no convincing difference and others claiming that video-assisted thoracoscopic procedures to be superior 8,[20][21][22][23] .…”
Section: Epidemiologymentioning
confidence: 99%
“…Effect of parecoxib combined with thoracic epidural analgesia on pain after thoracotomy to thoracotomy (2), patients undergoing thoracotomy and VATS alike continue to experience chronic pain at an alarmingly high incidence (3,4). Uncontrolled acute perioperative pain and related surgical stress responses are highly associated with poor outcomes after thoracotomy and predict the development of chronic pain (3,5).…”
Section: Introductionmentioning
confidence: 99%